The relationship between job satisfaction and emotional intelligence among secondary school teachers in Kuching, Sarawak / Syed Khairulhisham Syed Yusuf - Syed Yusuf, Syed Khairulhisham (2011)
This study intends to examine the relationship between job satisfaction and emotional intelligence among teachers in Kuching, Sarawak. The other objective is also identify the level of job satisfaction and emotional intelligence among the teachers in Kuching, Sarawaktoo. The data was collected through survey method by using questionnaire method to school teachers. Samples in this study secondary school teachers in Kuching, Sarawak which is chosen by using simple random method. The instrument used in this research was adapted from Job Satisfaction Survey (JSS) and Wong and Law emotional Intelligence Scale (WLEIS) which adapted from Spector (1997) and Wong and Law (2002) respectively. The questionnaire has been modified to suit the objective of the research. Statistical Package for Social Science (SPSS) version 17 has been used to interpret the data. The data was interpreted by using descriptive and correlational statistics. The evidence found in this research that teachers were moderately satisfied with their nature of job and the teachers were highly intelligence in their emotions. In explaining relationship, there was positive correlation but low in relationship between JS and EQ.